Starlight Optical: embracing all that glitters? - Soon, Jan Jan (2017)
Tracy hung up the phone, and twirled her pen nervously.She then paced up and down her office restlessly.She just got off the phone with one of the salesmen.He was urgently pushing for her decision to whether or not to place any orders for an assortment of top designer eyewear. It was to be an assortment that was rather exclusive by the Malaysian eyewear retail industry standard. To compound to the urgency of her decision, it was not every day that salesmen carrying such top designer eyewear would travel all the way to small towns like Changlun to promote such products.It was only due to intense road-shows by the top brands, as part of their concerted large-scale promotion in Asia, that the salesmen were carrying such exclusive high-end brands. If Tracy were to postpone her decision and not place any orders, it could be a long wait for her before the next chance came by.That was why Tracy had to make up her mind overnight, though she had been mulling over it for the past week.